2020
DOI: 10.1029/2020gl087648
|View full text |Cite
|
Sign up to set email alerts
|

Marshland Loss Warms Local Land Surface Temperature in China

Abstract: China has the third largest area of marshland in the world. Due to the effects of human activities, marshland in China has been widely converted to built‐up land (BL) and cultivated land (CL) during the past decades. Using satellite measurements of land surface temperature (LST), this study investigated the biophysical effects of marshland loss on LST. The results showed that marshland conversion to BL could increase the LST during both the daytime and nighttime. Conversion from marshland to CL could increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…At present, studies on vegetation response to climate change mostly focus on forest and grassland vegetation, and the research on the effect of climate change on marsh vegetation is relatively less (T. Chen et al., 2020; Erwin et al., 2009; Ji et al., 2020; Neubauer et al., 2013; Ross et al., 2013; D. Wei et al., 2017). The environmental conditions are different between marsh ecosystem and other ecosystems (Czapla et al., 2020; X. D. Wei et al., 2018), which may cause obviously different responses of vegetation to climate change (X. Shen et al., 2020a; Y. J. Wang et al., 2020). For a better understanding the correlation between vegetation and climate, it is of importance to explore the response of marsh vegetation to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies on vegetation response to climate change mostly focus on forest and grassland vegetation, and the research on the effect of climate change on marsh vegetation is relatively less (T. Chen et al., 2020; Erwin et al., 2009; Ji et al., 2020; Neubauer et al., 2013; Ross et al., 2013; D. Wei et al., 2017). The environmental conditions are different between marsh ecosystem and other ecosystems (Czapla et al., 2020; X. D. Wei et al., 2018), which may cause obviously different responses of vegetation to climate change (X. Shen et al., 2020a; Y. J. Wang et al., 2020). For a better understanding the correlation between vegetation and climate, it is of importance to explore the response of marsh vegetation to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DTR is considered as an important indicator and is receiving much more attention in regional and global scale in recent times [7][8][9][10]. Previous studies have reported that DTR changes were not uniform globally, which was attributed to complicated interactions of local climatic and anthropogenic factors [11,12]. In most parts of world, it is reported that DTR decreased with individual rate, such as in Bangladesh [13], Australia [14], and United States [15].…”
Section: Introductionmentioning
confidence: 99%
“…The ecosystem formed by "crop-soil-fertilizer" seems to continue indefinitely, but in each cycle, there is more or less natural loss, which needs to be replenished and controlled by human factors to continue the cycle [1][2][3][4][5][6]. Since its introduction in the 1980s, precision fertilization has been a significant constraint on balancing the contradiction between land resources, ecology, and population growth and a key technology for maintaining sustainable development [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%